Building social business ventures : insights from Muhammad Yunus, founder of the Grameen bank and Grameen family of companies - Yunus, Muhammad; Global academy for Entrepreneurship; Rooy Media; SKOLL Foundation (ASHOKA Innovators for the Public.)
Yunus here shares his strategies for building connections between business and social sectors.
DVD.
Keywords: Social change; Social entrepreneurship; Yunus, Muhammad 1940.